Sustainability Reporting: A Bibliometric Analysis of Knowledge Clusters and Hotspots (2000–2026) - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure, knowledge clusters, and emerging research hotspots in sustainability reporting literature through a comprehensive bibliometric analysis covering the period 2000–2026. Data were retrieved from the Scopus database using relevant keywords related to sustainability reporting, ESG, CSR disclosure, and non-financial reporting. The analysis was conducted using VOSviewer to examine keyword co-occurrence, overlay visualization, density mapping, and collaboration networks. The findings reveal that sustainability and sustainable development serve as the central themes, indicating their dominant role in shaping the research landscape. The results also show a significant shift from traditional corporate social responsibility toward ESG-oriented frameworks and governance-based reporting practices. Emerging hotspots such as circular economy, environmental management, and sustainable investments highlight the growing emphasis on impact-oriented and value-driven sustainability. Furthermore, the study identifies underexplored areas related to decision-making processes and environmental impact assessment, suggesting directions for future research. This study contributes to the literature by providing a systematic and longitudinal mapping of sustainability reporting research, offering insights for academics, policymakers, and practitioners in understanding its evolution and future trajectory.